ANALISIS PENGODEAN DIAGNOSA UTAMA BERDASARKAN ICD 10 DI RUMAH SAKIT UMUM DAERAH (RSUD) dr. RASIDIN PADANG - Afdhal Dinil Haq; Sayati Mandia; Dewi Oktavia (Iris Journal of Health Information Management, 2021)
Coding is one of the competencies of medical records which has a very important role in supporting the improvement of the quality of health services. Coding of an accurate, complete and consistent diagnosis will produce quality data. Quality of coded data is important for Health Information Management personnel because it is not only related to the quality of health services but also related to claiming costs and hospital development in the future. this was done at the Regional General Hospital dr. Rasidin Padang in January 2019. This study aims to determine the most major diagnoses based on ICD 10 at dr. Rasidin Padang in 2019. This study used a retrospective descriptive method with a quantitative approach. The research design used in this study was a descriptive cross-sectional study. The population used by all patient medical record files in January 2019 was 295 medical record files. The results of this study showed that the top five main diagnoses in January 2019 were, 18 patients with dengue haemorrhagic fever (DHF), 17 patients with Bronchopneumpnia, 14 patients with Diabetes Mellitus, 11 patients with Hyperemesis Gravidarum and 10 patients with Benign Neoplasm.